Morphology, complete mitochondrial genome and molecular phylogeny of Heterakis pucrasia sp. n. (Nematoda: Ascaridida) from the koklass pheasant Pucrasia macrolopha (Lesson) (Galliformes: Phasianidae) in Pakistan - Yousaf, Muhammad Amjad; Sun, Yi-Nuo; Chen, Hui-Xia; Khan, Asmat Ullah; Li, Liang (Frontiers in Veterinary Science, 2025)
Species of Heterakis (Ascaridida: Heterakoidea) are commonest nematode parasites occurring in the alimentary canal of wild and domestic birds, which are of major socio-economic importance, due to some Heterakis species causing Heterakidosis in wild birds and poultry. In the present study, a new species of Heterakis, H. pucrasia sp. n., was described using integrated methods based on specimens collected from the koklass pheasant Pucrasia macrolopha (Lesson) (Galliformes: Phasianidae) in Pakistan. The complete mitochondrial genome of H. pucrasia sp. n. was sequenced and annotated for the first time to enrich the mitogenomic data, and reveal the pattern of mitogenomic evolution of the family Heterakidae. Moreover, phylogenetic analyses of the orders Ascaridida, Spirurida, Oxyurida and Rhigonematida based on the amino acid sequences of 12 protein coding genes (PCGs) of mitochondrial genomes, revealed that the order Ascaridida is not monophyletic, and the superfamily Heterakoidea has a closer affinity with Rhigonematida + Oxyurida + Spirurida, than the superfamily Ascaridoidea in Ascaridida. The present findings enriched the global species composition of heterakid nematodes and their mitogenomic data, and also provided novel insight on the phylogenetic relationships between Heterakoidea and its related groups.